Flora : a novel - Godwin, Gail. (New York : Bloomsbury, 2013)
Ten-year-old Helen and her summer guardian, Flora, are isolated together in Helen's decaying family house while her father is doing secret war work in Oak Ridge during the final months of World War II. Their relationship and its fallout, played against a backdrop of a lost America will haunt Helen for the rest of her life.
Keywords: Girls -- Fiction; Guardian and ward -- Fiction; Bildungsromans